Restauration Fonctionnelle du Rachis : Effet du Niveau Initial de Douleur sur Les Performances des Sujets Lombalgiques Chroniques - Isabelle Caby; N Olivier; F Mendelek; R Bou Kheir; J Vanvelcenaher; P Pelayo (Pain Research and Management)
BACKGROUND: Chronic low back pain is a persistent lumbar pain of multifactorial origin. The initial pain level remains poorly used to analyze and compare responses in low back pain patients in a reconditioning program.